2022
DOI: 10.1183/16000617.0134-2022
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in lung diseases and ageing

Abstract: The lungs face ongoing chemical, mechanical, biological, immunological and xenobiotic stresses over a lifetime. Advancing age progressively impairs lung function. Autophagy is a “housekeeping” survival strategy involved in numerous physiological and pathological processes in all eukaryotic cells. Autophagic activity decreases with age in several species, whereas its basic activity extends throughout the lifespan of most animals. Dysregulation of autophagy has been proven to be closely related to the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…During the process of lysosome-dependent autophagy, damaged organelles, aggregated proteins, and degraded cytoplasmic debris accumulate within autophagic vacuoles ( Gao et al ., 2022 ; Zhang et al ., 2022 ). Autophagy has been recognized to play roles in the regulatory and developmental phases of lung damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the process of lysosome-dependent autophagy, damaged organelles, aggregated proteins, and degraded cytoplasmic debris accumulate within autophagic vacuoles ( Gao et al ., 2022 ; Zhang et al ., 2022 ). Autophagy has been recognized to play roles in the regulatory and developmental phases of lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy lung tissue, mTOR activation occurs, leading to the downregulation of LC3 II, an autophagy-related protein. However, in cases of lung damage, human bronchial epithelial cells exhibit upregulated LC3 II expression along with mTOR downregulation ( Zhang et al ., 2022 ). Notably, the downregulation of phosphorylated mTOR (p-mTOR) induced by lipopolysaccharide (LPS) is observed when TLR4 or MyD88 is knocked down.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies exploring the roles of autophagy in pulmonary diseases have been reported [ 95 , 105 , 106 ]. These data suggest that autophagy and mitophagy can play both protective as well as detrimental roles in human pulmonary diseases, in a cell type-specific manner [ 107 , 108 ].…”
Section: Copd and Autophagy/mitophagymentioning
confidence: 99%
“…Autophagy is a complex process that is regulated by a series of protein complexes and signaling pathways. In mammals, the core autophagy-related (ATG) genes and their protein products are generally classified into the ULK1 protein kinase complex [28], Vps34-beclin1 class III PI3-kinase complex [29,30], ATG9A transportation system [31,32], ATG12 conjugation system [33], and LC3 conjugation system [34]. Table 2 illustrates the components and role of autophagy complexes participating in the mammalian autophagy machinery.…”
Section: Mammalian Autophagy Machinery and Autophagy-related Genesmentioning
confidence: 99%